2018
DOI: 10.1038/s41586-018-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Aspm knockout ferret reveals an evolutionary mechanism governing cerebral cortical size

Abstract: The human cerebral cortex is distinguished by its large size and abundant gyrification, or folding, yet the evolutionary mechanisms driving cortical size and structure are unknown. While genes essential for cortical developmental expansion have been identified from the genetics of human primary microcephaly (“small head”, associated with reduced brain size and intellectual disability)1, studies of these genes in mice, whose smooth cortex is one thousand times smaller than that of humans, have provided limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
154
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(168 citation statements)
references
References 43 publications
2
154
0
Order By: Relevance
“…Their brain size is significantly increased compared to rodents (Barnette et al, 2009;Raju et al, 2018). Like humans, and unlike rodents, they possess a gyrencephalic cortex (Barnette et al, 2009;Duque & McCormick, 2010;Johnson et al, 2018). Furthermore, they undergo extensive postnatal brain development (McConnell, 1985(McConnell, , 1988Morton et al, 2017).…”
mentioning
confidence: 99%
“…Their brain size is significantly increased compared to rodents (Barnette et al, 2009;Raju et al, 2018). Like humans, and unlike rodents, they possess a gyrencephalic cortex (Barnette et al, 2009;Duque & McCormick, 2010;Johnson et al, 2018). Furthermore, they undergo extensive postnatal brain development (McConnell, 1985(McConnell, , 1988Morton et al, 2017).…”
mentioning
confidence: 99%
“…56,57 Thus, variation in ventricular volume may affect the circulation of growth factors that could potentially influence the regulation of cerebral cortical development. Alternatively, because ASPM has a significant effect on neural progenitor cycling along the ventricles in fetal life, 26,59 the association shown in our study may be a result of how brain size is patterned by ASPM during neurogenesis in early development. It has been shown that ASPM plays a role in regulating the affinity of ventricular radial glial cells (VRGs) for the ventricular surface.…”
Section: Discussionmentioning
confidence: 77%
“…Alternatively, because ASPM has a significant effect on neural progenitor cycling along the ventricles in fetal life,26,59 the association shown in our study may be a result of how brain size is patterned by ASPM during neurogenesis in early development. Alternatively, because ASPM has a significant effect on neural progenitor cycling along the ventricles in fetal life,26,59 the association shown in our study may be a result of how brain size is patterned by ASPM during neurogenesis in early development.…”
mentioning
confidence: 77%
See 2 more Smart Citations